Attachment and Defense Mechanisms in subjects diagnosed with Borderline Personality Disorder - Καλαματιανός Αντώνιος; Κανελλοπούλου Λίσσυ (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The interest with regard to the Borderline Personality Disorder (BPD) has increased in the past few years, because the number of people with the aforementioned diagnosis who use mental health services has risen. The study aimed at examining the defense mechanisms in people with BPD diagnosis in relation to the attachment type they adopt. The sample consisted of 36 adult subjects diagnosed with BPD who attended psychiatric outpatient departments and 36 people who attended the ophthalmologic outpatient care at a general hospital. The adult attachment questionnaire CA-MIR and the Defense Style Questionnaire-40 were administered to the participants. In general, results are in accordance with the theoretical background, because it was demonstrated that diagnosed subjects scored higher in the insecure attachment types, that is, the ambivalent, the detached and the non-resolved, whereas the non-diagnosed scored higher in the autonomous attachment. Moreover, diagnosed subjects used more than the non-diagnosed participants the neurotic and the immature defenses, but they did not differ with respect to mature defenses. Finally, correlations between attachment and defenses were found with the exception of the mature that correlated with no attachment model. These findings may contribute to the identification of factors that participate in BPD and in the configuration of more efficient therapeutic interventions.